The Use of Participant Recollection in the Modeling of Organizational Decision Process - Schwenk, Charles R. (Academy of Management Review, 1985)
Two fundamental differences exist between models of organizational decision processes based on participant recollection and those based on other data sources such as analysis of meeting transcripts, archival data, and field observation. These differences are illustrated with a number of specific decision process models. Possible reasons for the differences in models developed from alternative data sources are outlined. Implications for decision process research are discussed.